Kesenjangan Kepesertaan Jaminan Sosial Tenaga Kerja di Indonesia : Analisis Data Sakernas 2018 - Yanti Astrelina Purba; Yulinda Nurul Aini; Devi Asiati; Ngadi Ngadi (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2020)
Increasing the participation of Labor Social Security in Indonesia has become the government's commitment. However, until now, there are still many workers who have not participated in labor social security. This paper aims to analyze the gap in the social security membership of workers in Indonesia. Data for analysis is SAKERNAS, August 2018 issued by BPS. Data analysis was carried out by descriptive analysis with both tables and graphics. The results of the analysis show that the participation of workers in labor security in Indonesia is 41.45%. Disparities in labor social security membership occurred in the formal and informal sectors of 48.92% and 1.13%, respectively. Disparities in labor security membership also occur according to main industry, province of residence, gender, and level of education. By sector, the lowest participation occurred in the construction and accommodation sector (20.26%), while the highest participation was in the electricity and gas sector (72.26%). For workers with a diploma education and above, labor security participation is 64.34%, while in junior high school and below, the participation is 19.55%. The participation of labor security in casual workers is still low. Limited income is the main obstacle for informal sector workers and free workers to participate in Labor Social Security. For this reason, it is necessary to think about a subsidized financing scheme so that labor social security does not burden the informal sector workers.